ANTHROPOMETRIC PROFILE OF THE FEMALE FUTSAL ATHLETS PARTICIPANTS OF THE STATE UNDER 17 CHAMPIONSHIP IN MOSSORO-RN. (Fiep Bulletin - online, 2014)
Futsal is a sport characterized by variable intensity intermittent exercise that involves aerobic and anaerobic activity both during training and in the game. You need agility in the actions of athletes who are prepared to respond to many different stimuli, the faster and more efficient. The purpose of this descriptive study was to evaluate the anthropometric profile of 40 female athletes, aged 14-17 years who participated in the State Championship Futsal Women under 17 in the town of Mossoró-RN. Part of the sample group is the current vice-champion of the special division of the Brazilian futsal league. Was used as measuring instruments, a stadiometer (height), a digital scale (weight), tape measure, calipers one (skinfolds), both brand SANNY. The fat percentage was determined using the equation proposed by Slaughter et al, (1988), using the sum of triceps and subscapular skinfolds. Were considered inadequate fat percentages below average ( 15%). During the application of the instruments, was guarded to protect the privacy and anonymity of the participant in the presentation of results. The analyzed data allow us to conclude that the athletes classified according to BMI are normal weight, fat percentage as to the athletes showed values ??above 15% classified as above average.
Keywords: Anthropometric profile; Futsal Women